Study of soft tissue reconstruction in postburn flexion contracture of the hand - Gareikpatii, Nagaraj (International Surgery Journal, 2021)
Background: Burn contracture of the hand can leave patients with severe functional and psychological limitations. This study evaluates the severity of the deformity and various reconstructive options in post-burn hand injuries. Methods: This work includes the study of 50 patients who underwent reconstruction for post-burn flexion contracture of the hand, including fingers, in the department of plastic surgery. The patients were treated between April 2007 to April 2009. Results: Males were more commonly affected by burn injuries and thermal burns were more common than electrical burns. The little finger showed higher involvement and contracture release followed by grafting was the commonly done reconstructive procedure. Conclusions: Split thickness skin graft (SSG) were more effective in reconstruction in thermal injuries, while cross finger flaps (CFF) showed more promise in electrical injuries of the hand.